Organizational innovation and its influence on electronic commerce - Lozano Magdaleno, Jesús Aarón; Robles Parra, Jesús Martín (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
Electronic commerce has become a crucial element for the competitiveness and comercial prosperity of organizations, being a growing demand among consumers in an era of globalization and virtualization. Organizational innovation helps organizations to go through e-commerce adoption processes through new methods in Jobs, business practices and external relations. This research reviews the theorical fundations that establish organizational innovation as a response to the intangible demands of the market, thus helping to move towards the adoption of electronic commerce.